Alite-belite-ye'elimite cements: Effect of dopants on the clinker phase composition and properties - Zea-Garcia, Jesus D.; García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel (My University, 2018)
Clinkers with alite-belite-ye'elimite (ABY) are considered as eco-friendly cements. Clinkering (2 Kg) of two types of ABY clinkers was optimized: standard-ABY, with CaF2 and ZnO as dopants (32.6 wt% alite, 30.4 wt% β-C2S and 15.6 wt% ye'elimite) and αABY, with CaF2, ZnO, B2O3, Na2O (14.4 wt% alite, 37.1 wt% β-C2S, 18.5 wt% α′HC2S and 7.5 wt% ye'elimite). Zn and F were mainly incorporated in alite and ferrite as dopants determined by EDS semi-quantitative analysis. The effect of dopants on the hydration of the cement mortars has been tested. Thus, standard-ABY develops 29.9 MPa compressive strengths at 1 day while αABY does 16.8 MPa, mainly due to the higher amount of alite of the former. The presence of α′H-C2S in αABY increases mechanical strengths at 28 days of hydration from 44.7 MPa of standard-ABY to 74.9 MPa.
Keywords: Ciencia; Clinkering; Ca3SiO5; 3CaO·3Al2O3·CaSO4; C2S polymorphism; Boron; Fluor; Zinc; Alkaline oxides; X-ray diffraction & Rietveld method; EDS